Implementation of smart direct power control strategy based on M5-Pruned algorithm for three-phase pulse width modulation rectifier - Mujammal, Mujammal Ahmed Hasan; Moualdia, Abdelhafidh; Boudana, Djamel; Wira, Patrice; Cherifi, Abderrezzak (Energy (Oxford), 2025)
This paper suggests a smart direct power control (SDPC) strategy based on the M5-Pruned algorithm for a three-phase (PWM) rectifier. (PWM) rectifier is a non-linear system due to its structure of semiconductor switches that distort the current line, produce DC link fluctuations, degrade the unity power factor (UPF) and system stability. Conventional methods as the DPC model based on proportional-integral (PI) controllers and hysteresis comparators cannot effectively address the aforementioned drawbacks due to the limited bandwidth operations, overshoot response, tuning sensitivity, sluggish reaction to sudden changes, and variable switching frequency. This paper proposes a new DPC strategy that replaces the intelligent M5-Pruned algorithms instead with the DC bus voltage controller and the active and reactive hysteresis comparators. Fast prediction, large-scale control, update learning, and robustness are powerful features enabling M5P model accomplish the high and stable performance of the DC bus voltage and compensate for the hysteresis comparator defects. Under MATLAB/Simulink, WEKA software, and DSpace DS1103 board ordered by the graphical interface of the control desk, the simulation and experimental results achieved and proved the effectiveness, efficiency, and robustness of the proposed control in both steady and transient states. •A novel Direct Power Control (DPC) strategy is introduced, utilizing the M5-Pruned algorithm for enhanced control of a three-phase Pulse Width Modulation (PWM) rectifier.•The M5-Prunted algorithm exhibits superior characteristics, including fast prediction, large-scale control, simple training processes, and robust performance under varying conditions.•The proposed algorithm addresses and overcomes major limitations of classic DPC methods, significantly reducing ripples and improving system performance.•Both simulation and experimental results demonstrate the high effectiveness, efficiency, and robustness of the proposed DPC strategy based on the M5-Pruned algorithm.